(untitled) (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study discusses the phenomenon of cyberbullying as a form of aggressiveness in the digital era, which is increasingly prevalent among adolescents. Adolescence is a critical stage of psychological and social development in which individuals are vulnerable to becoming both perpetrators and victims of cyberbullying due to exposure to negative content on social media and a lack of parental supervision. This study employs a qualitative approach using a literature review method to examine theories and previous findings related to cyberbullying among adolescents. The results indicate that these forms of aggressiveness have significant negative impacts on adolescents’ psychological and social well-being, including feelings of fear, anxiety, depression, and decreased self-confidence. Therefore, preventive efforts are necessary, including increased parental supervision and improved digital literacy, in order to create a safer and healthier digital environment for adolescents.